Spectral analysis of the AMXP IGR J17591–2342 during its 2018 outburst. Issue 2 (19th December 2022) - Manca, A; Gambino, A F; Sanna, A; Jaisawal, G K; Di Salvo, T; Iaria, R; Mazzola, S M; Marino, A; Anitra, A; Bozzo, E; Riggio, A; Burderi, L
ABSTRACT: The Accreting Millisecond X-ray Pulsar IGR J17591–2342 is a Low Mass X-ray Binary (LMXB) system that went in outburst on 2018 August and it was monitored by the NICER observatory and partially by other facilities. We aim to study how the spectral emission of this source evolved during the outburst by exploiting the whole X-ray data repository of simultaneous observations. The continuum emission of the combined broad-band spectra is on average well described by an absorbed Comptonization component scattering blackbody-distributed photons peaking at (0.8 ± 0.5) keV by a moderately optically thick corona (τ = 2.3 ± 0.5) with temperature of (34 ± 9) keV. A blackbody component with temperature and radial size of (0.8 ± 0.2) keV and (3.3 ± 1.5) km, respectively, is required by some of the spectra and suggests that part of the central emission, possibly a fraction of the neutron star surface, is not efficiently scattered by the corona. The continuum at low energies is characterized by significant residuals suggesting the presence of an absorption edge of O viii and of emission lines of Ne ix ions. Moreover, broad Fe i and Fe xxv Kα emission lines are detected at different times of the outburst, suggesting the presence of reflection in the system.